Influence of dietary vitamin A restriction on metabolism and transcription of genes related to lipogenesis in Iberian pigs - Ayuso, M.; Isabel, B.; Rey, A.I.; Fernández, A.; Segura, J.; Benítez, R; Silió, L; Daza, A.; Óvilo, C.; López-Bote, C.J (Revista Complutense de Ciencias Veterinarias, 2013)
Vitamin A is a liposoluble vitamin obtained from the diet with multiple physiological actions in all animal tissues, including an antiadipogenic action which seems to be limited to muscular tissues. Thus, vitamin A restriction has been proposed as a strategy for improving meat and carcass quality in farm animals. In this work we have studied the effects of vitamin A dietary restriction on productive traits, tissue fatty acid composition and expression of a panel of adipogenic and lipogenic candidate genes in Iberian pigs. Forty Torbiscal pigs were fed with a standard or a Vitamin A restricted diet from two months of age till their sacrifice conducted in two batches, at 100 and 160 Kg live weight. Diet had no significant effect on growth, fatness, yields or intramuscular fat, but animals receiving no vitamin A supplementation showed higher monounsaturated fatty acids and lower saturated fatty acids in back fat and loin samples than the control ones. Adipose tissue SCD gene expression was higher in vitamin A restricted animals, as occurs with CRABP II expression. On the other hand, RXRG expression was higher in control group, in agreement with the influence on transcription of retinoic acid and its potential relationship with adipogenesis and lipogenesis.